Assessment of dental caries among a group of institutionalized orphan children compared to parented school children: case–control study - Nagwa Mohamed Ali Khattab; Mennat Allah Ashraf Abd-Elsabour (BMC Oral Health, 2023)
Abstract Background It has been well documented that the absence of family support influences the general and oral health of children. Literature regarding the oral health status of institutionalized orphan children, who lost their families' support, especially in Egypt, remains vague. Therefore, the current study was carried out to assess dental caries among two groups of institutionalized orphan children, and compare their results with a group of parented school children in Giza, Egypt. Methods A total of 156 children were included in this study, residing in a non-governmental orphanage, a governmental orphanage, and parented children attending private primary school. Written informed consent was obtained before the start of the study from the legal guardians or the child's parent. The dental examination was carried out as recommended by the WHO. DMF and def indices were used to assess dental caries for primary and permanent teeth. Also, the unmet treatment needs index, care index, and significant caries index were calculated. Results The results revealed that mean values for DMF total score were 1.86 ± 2.96, 1.80 ± 2.54, and 0.7 5 ± 1.29 for, non-governmental, governmental orphanages, and school children respectively. While the mean def total scores were 1.69 ± 2.58, 0.41 ± 0.89, and 0.85 ± 1.79 for non-governmental, governmental orphanages, and school children, respectively. There was a high level of unmet treatment needs, especially among orphans. The significant caries index was 2.5, 4.29, and 2.17 for, non-governmental, governmental orphanages, and school children, respectively. Conclusions Within the limitation of this case–control study, the institutionalized orphanage children had a high prevalence of dental caries and worse caries experience compared to parented school children. Effective oral health preventive strategies are required to improve the oral health status and oral health practices of those children. Trial registration The trial was registered on ClinicalTrial.gov (ID: NCT05652231).